Discovery and ramifications of incidental Magnéli phase generation and release from industrial coal-burning - Yi Yang (Nature Portfolio, 2017)
Solid-state emissions from coal burning remain an environmental concern. Here, the authors have found that TiO2 minerals present in coal are converted into titanium suboxides during burning, and initial biotoxicity screening suggests that further testing is needed to look into human lung consequences.